FORMULASI DAN UJI STABILITAS GRANUL EFERVESEN SARI BUAH SIRSAK (Annona muricata L.) - - Prasetyorini; Ike Yulia Wiendarlina; Murni Tiradisuci (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2015)
This event will be based on research by the large number of reports on the benefits of soursop for various diseases especially antihipertensi and antihiperuresemia. Forms need to be developed so that a more practical preparations and ketersediannya continuous, one of which is in the form of effervescen granule juice. This research aims to find out whether the soursop fruit juice can be a formulation in granule material of efervesen who meet the requirements of quality, standards and terms of efervesen granule and making it acceptable in society. In the study of fruit juice made with the soursop fruit flesh filter using Batiste, juice drained using Freezedryer with the addition of maltodekstrin 20%. The powder is then made 3 fruit formula granule effervesent with the difference of acid-catalyzed and the manufacturing process is done by the method of smelting using alcohol 70% without binder. Test results show the BSLT fruit pollen have toxic effects against larvae of shrimp Artemiasalina Leach with LC50 108.914 ppm. The results of the evaluation of the third shows the formula for granule corner quietly and solubility are eligible, cohesive, and the granule flow values test froth above 70%, the test results of licentious formula2 has the most preferred taste. Stability test for efervesen granule 8 weeks the most stable at a temperature of 15 Â° C containing Sodium ion levels 3, 97g/100 ggranul, potassium of 0, 24g/100 ggranul, 2, 19mg SAG polyphenols/ggranul and vitamins C51, 91mg/100ggranul.Â Key words : granul, efervesen, stabilitas, sirsak